OPTIMIZATION OF MUTAGEN DOSE FOR EARLY SEEDLING YIELD ASSOCIATED QUANTITATIVE CHARACTERS IN CANOLA GERM PLASM - BANO , Z; QURESHI , ST; MEMON , RA; AHMED , I (Biological and Clinical Sciences Research Journal, 2024)
Pakistan is facing vital shortage in supply of health promoting crops used as vegetable as well as oil source. Brassica napus (Canola) is such a rich crop that occupy an important position in the oilseed crops of world but unfortunately in Pakistan its germ plasm needs genetic improvement due to narrow gene pool. Mutagenesis is a powerful tool for introducing new alleles, therefore different doses of Gamma radiations (750Gy, 1000Gy, 1250Gy) and EMS (0.5%, 1.0% and 1.5%) were used to induce genetic diversity for early yield associated quantitative characters in two Canola genotypes (Hyola-41 and Shiralee). The data was recorded for days to flowering, days to maturity, plant height, number of branches per plant and pod length in M2 and M3 generation. Significant (p≤0.05) variations were observed for most of phenotypic parameters for both mutagens. The mean value of all the phenotypic parameters in M2 generation increased with moderate dose of EMS and Gamma rays in both genotypes as compared to respective controls. whereas in M3 generation both genotypes were more responsive to Gamma rays (1000 Gy) for all studied characters except early maturity in both tested genotypes. Heritability analysis exhibited high heritability and high genetic advance for most of the traits by moderate and highest does of Gamma rays, while reverse is true for EMS in both generations for Shiralee.